Rural Transport Services Indicators: Using a new mixed-methods methodology to inform policy in Ghana - Krijn Peters (Transportation Research Interdisciplinary Perspectives, 2019)
Rural people need access to markets and services. In developing countries, where private vehicle ownership is limited, villagers depend on public transport services. However, research evidence available to inform policy formulation is often extremely limited. To better understand the characteristics, costs, frequencies and acceptability of rural transport services in Ghana, data was collected using a methodology developed by the International Forum for Rural Transport and Development. This methodology combines traffic count data with structured qualitative interviews with transport users, operators, regulators and local development experts. A key finding concerned motorcycle taxis which, although officially banned in 2012, remain a common sight in rural Ghana and are generally appreciated by transport users and other stakeholders. Following our presentation of findings to an audience of national stakeholders and policy-makers, a consensus emerged to continue restricting commercial motorcycle operations in cities and on highways, but allowing them on rural roads, if combined with appropriate safety training and regulations. These findings feed into an ongoing policy debate about motorcycle taxi transport in Sub-Saharan Africa.